Method for producing a superabsorbent resin composite

JP7652458B2Active Publication Date: 2025-03-27LG CHEM LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023539359
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-07-12
Filing Date
2023-01-12
Publication Date
2025-03-27
Estimated Expiration
2043-01-12

Smart Images

  • Figure 0007652458000004
    Figure 0007652458000004
  • Figure 0007652458000001
    Figure 0007652458000001
  • Figure 0007652458000002
    Figure 0007652458000002
Patent Text Reader

Abstract

The present invention provides a method for producing a superabsorbent resin composite, comprising the steps of: preparing superabsorbent resin particles containing a crosslinked polymer of a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group and an internal crosslinking agent; hydrating the superabsorbent resin particles to adsorb moisture onto the superabsorbent resin particles; and mixing the hydrated superabsorbent resin particles with an anti-caking agent and attaching the anti-caking agent onto the hydrated superabsorbent resin particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0085865, filed on July 12, 2022, and all contents disclosed in the documents of said Korean patent application are incorporated by reference into this specification.

[0002] The present invention relates to a method for producing a superabsorbent resin composite, and more particularly to a method for producing a superabsorbent resin composite in which moisture is adsorbed on the surfaces of superabsorbent resin particles by a hydration treatment, thereby improving the anti-caking efficiency of an anti-caking agent. [Background technology]

[0003] Super absorbent polymer (SAP) is a synthetic polymeric substance that has the ability to absorb about 500 to 1,000 times its own weight in water, and different developers give it different names, such as SAM (Super Absorbency Material) and AGM (Absorbent Gel Material). Such super absorbent polymers have started to be put to practical use as sanitary products, and are currently widely used as soil water retention agents for horticulture, water stoppers for civil engineering and construction, seedling sheets, freshness maintaining agents and steaming materials in the food distribution field, and are mainly used in the field of sanitary materials such as diapers and sanitary napkins.

[0004] Since superabsorbent resin is a polymer with the property of absorbing water, caking occurs in areas with high humidity, and to prevent this phenomenon, anti-caking agents are added. Anti-caking agents are generally inorganic substances that do not absorb water. Inorganic substances are also used as additives to improve permeability by preventing aggregation between superabsorbent resin particles.

[0005] However, when the inorganic material is dry mixed with the superabsorbent resin particles and applied to the surface of the superabsorbent resin particles, the application efficiency is low due to the weak attractive force between the superabsorbent resin particles and the inorganic material, which causes problems such as the generation of superabsorbent resin dust particles and reduced anti-caking efficiency. Summary of the Invention [Problem to be solved by the invention]

[0006] The problem to be solved by the present invention, in order to solve the problems mentioned in the background of the invention above, is to provide a method for producing a superabsorbent resin composite having improved anti-caking efficiency by subjecting superabsorbent resin particles to a hydration treatment to adsorb moisture onto the surfaces of the superabsorbent resin particles, and mixing the superabsorbent resin particles with the moisture adsorbed thereon with an anti-caking agent. [Means for solving the problem]

[0007] According to one embodiment of the present invention for solving the above problems, the present invention provides a method for producing a superabsorbent resin composite, the method including the steps of: preparing superabsorbent resin particles containing a crosslinked polymer of a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group and an internal crosslinking agent; hydrating the superabsorbent resin particles to adsorb moisture into the superabsorbent resin particles; and mixing the hydrated superabsorbent resin particles with an anti-caking agent and attaching the anti-caking agent onto the hydrated superabsorbent resin particles. Effect of the Invention

[0008] According to the method for producing a superabsorbent resin composite of the present invention, in order to increase the bond between the superabsorbent resin particles and the anti-caking agent, a hydration treatment is further performed before the mixing process of the superabsorbent resin particles and the anti-caking agent, thereby improving the adhesive strength between the superabsorbent resin particles and the anti-caking agent, thereby improving the anti-caking efficiency. In addition, the hydration treatment allows the anti-caking agent to be uniformly applied and attached to the superabsorbent resin particles, thereby reducing the dust issue of the superabsorbent resin fine particles. [Brief description of the drawings]

[0009] [Figure 1] 1 is a process flow chart of a method for producing a superabsorbent resin composite according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The terms and words used in the description of the present invention and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0011] In the following, the present invention will be described in more detail in order to facilitate understanding of the present invention.

[0012] A method for producing a superabsorbent resin composite according to one embodiment of the present invention may include the steps of preparing superabsorbent resin particles containing a crosslinked polymer of a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group and an internal crosslinking agent, hydrating the superabsorbent resin particles to adsorb moisture into the superabsorbent resin particles, and mixing the hydrated superabsorbent resin particles with an anti-caking agent and attaching the anti-caking agent onto the hydrated superabsorbent resin particles.

[0013] The present invention will be described in detail with reference to FIG. 1. First, in the step of preparing the superabsorbent resin particles, the method for producing the superabsorbent resin particles is as follows. First, a composition is polymerized to form a hydrogel polymer. The composition may contain a water-soluble ethylenically unsaturated monomer, an internal crosslinking agent, and a polymerization initiator, and may further contain additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, as necessary.

[0014] Here, the water-soluble ethylenically unsaturated monomer may be (meth)acrylic acid or a salt thereof. For example, when using acrylic acid in which at least a portion of acrylic acid is neutralized and / or an alkali metal salt thereof such as a sodium salt thereof, it is possible to obtain highly water-absorbent resin particles having improved water absorption.

[0015] In addition, the water-soluble ethylenically unsaturated monomer may be an anionic monomer such as maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, or 2-(meth)acrylamido-2-methylpropanesulfonic acid, or a salt thereof; a nonionic hydrophilic monomer such as (meth)acrylamide, N-substituted (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxypolyethyleneglycol (meth)acrylate, or polyethyleneglycol (meth)acrylate; and an amino group-containing unsaturated monomer such as (N,N)-dimethylaminoethyl (meth)acrylate, or (N,N)-dimethylaminopropyl (meth)acrylamide, or a quaternary product thereof. The salt of the anionic monomer may be a metal salt, a divalent metal salt, an ammonium salt, or an organic amine salt.

[0016] The water-soluble ethylenically unsaturated monomer may include at least a partially neutralized acidic group. The ethylenically unsaturated monomer including at least a partially neutralized acidic group may be prepared by neutralizing the acidic group of the water-soluble ethylenically unsaturated monomer using a neutralizing agent. Here, the neutralizing agent may be a basic substance such as sodium hydroxide (or caustic soda), potassium hydroxide, or ammonium hydroxide that can neutralize the acidic group.

[0017] The superabsorbent resin particles may include a crosslinked polymer crosslinked by an internal crosslinking agent, which may crosslink and polymerize the unsaturated bonds of the water-soluble ethylenically unsaturated monomer.

[0018] The internal crosslinking agent may be a (meth)acrylate-based compound that undergoes a crosslinking reaction by a free-radical polymerization (FRP) reaction. Specifically, the internal crosslinking agent may be one or more compounds selected from the group consisting of ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate. More specifically, the internal crosslinking agent may be polyethylene glycol di(meth)acrylate.

[0019] Meanwhile, in the composition, the polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator by UV irradiation depending on the polymerization method. However, even in the photopolymerization method, a certain amount of heat is generated by UV irradiation, and a certain amount of heat is generated as the polymerization reaction, which is an exothermic reaction, proceeds, so a thermal polymerization initiator may also be included.

[0020] The photopolymerization initiator may be a compound capable of forming a radical by light such as ultraviolet light. The photopolymerization initiator may be at least one selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone. Specific examples of acyl phosphine include diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate.

[0021] The thermal polymerization initiator may be at least one selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide, and ascorbic acid.Specific examples of persulfate initiators include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), and ammonium persulfate ((NH4)2S2O8).

[0022] Specifically, polymerization methods are broadly divided into thermal polymerization and photopolymerization depending on the polymerization energy source. Thermal polymerization can be carried out in a reactor having a stirring shaft such as a kneader, and photopolymerization can be carried out in a reactor equipped with a movable conveyor belt.

[0023] The crosslinked polymer of the present invention may be prepared by polymerization of a composition including a water-soluble ethylenically unsaturated monomer, an internal crosslinking agent, and a polymerization initiator, and the internal crosslinking agent in the composition may be 0.01 to 5 parts by weight based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. For example, the internal crosslinking agent may be 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.2 parts by weight or more, and 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.5 parts by weight or less based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the content of the internal crosslinking agent is too low, crosslinking may not be sufficiently performed, making it difficult to achieve a strength above an appropriate level, and if the content of the internal crosslinking agent is too high, the internal crosslinking density may be high, making it difficult to achieve the desired water retention ability.

[0024] The composition of the present invention may be prepared in the form of a solution dissolved in a solvent. Here, the solvent that can dissolve the above-mentioned raw materials may be used. For example, the solvent may be water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide, or a mixture thereof.

[0025] Generally, superabsorbent resin particles containing crosslinked polymers prepared by polymerization of water-soluble ethylenically unsaturated monomers in the presence of an internal crosslinking agent have hydrophilic surfaces due to the unpolymerized acid groups (-COOH) and / or neutralized acid groups (-COO-). Due to the hydrophilic surface of the superabsorbent resin particles, when exposed to air, they absorb moisture from the air, and the moisture present between the superabsorbent resin particles causes capillary forces, hydrogen bonds, inter-particular diffusion, or van der Waals forces between particles, resulting in irreversible aggregation between particles. In addition, water is always used during the manufacturing process of superabsorbent resin particles, but due to the above problems, an additional grinding process is required during the process due to aggregation between particles, or a caking inhibitor is added to prevent aggregation.

[0026] Next, the hydrogel polymer formed by the polymerization reaction of the composition is dried, pulverized, and classified to obtain a base resin powder. Here, a coarse pulverization process can be further performed to increase efficiency when drying the hydrogel polymer. The pulverizer used in the coarse pulverization process can be any one selected from the group of pulverizing devices consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter.

[0027] A drying step can be carried out on the hydrogel polymer immediately after polymerization, which has been coarsely pulverized as described above, or has not been subjected to the coarse pulverization step. Specifically, the drying step can be carried out by a method of supplying hot air, irradiating with infrared rays, irradiating with ultrashort waves, or irradiating with ultraviolet rays. The water content of the polymer after such a drying step can be 0.05 to 10% by weight.

[0028] The dried polymer obtained through the drying step is then pulverized, and the pulverizer used in this step may be, for example, a ball mill, a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, or a jog mill.

[0029] In addition, after the pulverization step, in order to control the physical properties of the superabsorbent resin particles to be manufactured as a final product, the polymer powder obtained after pulverization can be classified according to particle size. Specifically, polymers having a particle size of 150 to 850 μm are classified into normal particles, and only the polymer powder having such a particle size can be manufactured as a product through a surface cross-linking reaction step described later. On the other hand, polymers having a particle size of less than 150 μm are classified into fine particles and eliminated because they cause phenomena such as gel blocking. A base resin powder can be obtained by such pulverization and classification steps.

[0030] Next, a surface cross-linking reaction step is performed to form a surface cross-linked layer on at least a part of the surface of the base resin powder in the presence of a surface cross-linking agent, where the surface cross-linked layer may be cross-linked from the surface cross-linking agent, the surface cross-linking agent may include a polyfunctional epoxy compound, and the polyfunctional epoxy compound may be a glycidyl ether compound of a polyhydric alcohol.

[0031] Specifically, the surface cross-linking agent may include one or more polyfunctional epoxy compounds selected from the group consisting of ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, triethylene glycol diglycidyl ether, tetraethylene glycol diglycidyl ether, glycerin polyglycidyl ether, and sorbitol polyglycidyl ether.

[0032] The surface cross-linking agent may be mixed with the base resin powder in a solution state, specifically in a surface cross-linking solution state dissolved in a solvent. The surface cross-linking solution may contain water and methanol in addition to the surface cross-linking agent. In general, the surface cross-linking solution is applied to the surface of the superabsorbent resin particles. Thus, the surface cross-linking reaction takes place on the surface of the superabsorbent resin particles, which does not substantially affect the inside of the particles, but improves the cross-linking property on the surface of the particles. Thus, the surface cross-linked superabsorbent resin particles have a higher degree of cross-linking near the surface than the inside. The surface cross-linking reaction and drying can be carried out simultaneously by heating the polymer to which the surface cross-linking agent has been added.

[0033] Finally, a step of classifying the base resin powder on which the surface cross-linked layer is formed can be performed. The base resin powder on which the surface cross-linked layer is formed can be completed as superabsorbent resin particles through processes such as pulverization and classification. Thereafter, the superabsorbent resin particles can be classified according to particle size, and superabsorbent resin particles of an appropriate particle size according to the intended use can be manufactured. In general, the particles are classified into surface cross-linked differential particles having a particle size of less than 150 μm and surface cross-linked normal particles having a particle size of 150 μm to 850 μm, and the surface cross-linked normal particles can be manufactured and used as the superabsorbent resin particles of the present invention.

[0034] Since the superabsorbent resin particles have a property of absorbing moisture, they absorb moisture from the air and aggregate together, resulting in a caking phenomenon. To prevent this phenomenon, an anti-caking agent is added. Conventionally, the anti-caking agent is dry-mixed with the superabsorbent resin particles having a surface cross-linked layer without any additional post-treatment, or the anti-caking agent is mixed into the surface cross-linking solution during the preparation of the superabsorbent resin particles to form a surface cross-linked layer.

[0035] Conventionally, when the anti-caking agent is dry mixed with the superabsorbent resin particles having a surface cross-linked layer without a separate post-treatment, the coating efficiency is reduced due to the weak attractive force between the superabsorbent resin particles having a surface cross-linked layer and the anti-caking agent, and the anti-caking agent may be detached during transportation or handling in the process. In this case, the dust issue of the superabsorbent resin particles increases significantly, and the anti-caking efficiency is reduced. Here, the anti-caking efficiency means the degree to which caking (i.e., a state in which the superabsorbent resin particles are aggregated due to aggregation) is prevented and how long such a state can be sustained. The coating efficiency means the degree of coating uniformity of the anti-caking agent that is applied and attached to the superabsorbent resin particles.

[0036] Furthermore, in the past, when a surface-crosslinked layer was formed by mixing an anti-caking agent into a surface-crosslinking solution, there was a problem that the surface crosslinking efficiency was reduced due to a change in viscosity of the surface-crosslinking solution, and as a result, the absorption rate of the highly water-absorbent resin was reduced.

[0037] In contrast, in the present invention, the superabsorbent resin particles having a surface cross-linked layer formed thereon are further subjected to a hydration treatment, and then mixed with an anti-caking agent, thereby increasing the surface adhesive strength between the superabsorbent resin particles and the anti-caking agent without reducing the moisture absorption effect of the superabsorbent resin particles against moisture, thereby making it possible to significantly reduce the phenomenon of detachment and scattering of the superabsorbent resin fine particles.

[0038] For this purpose, according to one embodiment of the present invention, a step of hydrating the superabsorbent resin particles prepared by the above-mentioned process to adsorb moisture into the superabsorbent resin particles can be performed. The hydration process is a process of adsorbing a certain amount of moisture onto the surfaces of the superabsorbent resin particles, and can be performed, for example, by placing the superabsorbent resin particles in a sealed container at normal pressure in a high temperature and high humidity atmosphere for a predetermined period of time. Meanwhile, the moisture adsorbed onto the surfaces of the superabsorbent resin particles can be diffused and absorbed into the superabsorbent resin particles over time.

[0039] The hydration treatment can be carried out under conditions of 25°C to 80°C, specifically 40°C to 60°C. This allows the appropriate amount of moisture around the highly absorbent resin particles to be maintained, enabling smooth hydration treatment. When the temperature is 25°C or higher, moisture can be adsorbed onto the surface of the highly absorbent resin particles, increasing the efficiency of the hydration treatment. When the temperature is 80°C or lower, excessive water vapor can be prevented from being generated, and there is an effect of preventing caking between particles that occurs when moisture (water vapor) is adsorbed onto the surface of the highly absorbent resin particles and then absorbed into the inside.

[0040] Specifically, the hydration temperature may be the internal temperature of a thermo-hygrostat described below when the hydration process is performed in the thermo-hygrostat, and may be the temperature of the droplets when the hydration process is performed by spray hydration.

[0041] According to an embodiment of the present invention, the hydration treatment may be performed under a condition of 50% RH to 95% RH, specifically, under a condition of 80% RH to 90% RH. Here, the "% RH" is a unit of relative humidity, and is a percentage of the current amount of water vapor when the maximum amount of water vapor that can be contained at a certain temperature (i.e., saturated water vapor) is set to 100. If the relative humidity is less than 50% RH, it may be difficult to form and maintain water vapor due to the too low humidity, and it may be difficult to hydrate the superabsorbent resin particles with the appropriate amount of water vapor, i.e., moisture. As a result, the adhesive force between the anti-caking agent described below and the superabsorbent resin particles may weaken, causing detachment. If the relative humidity is more than 95% RH, moisture may be excessively adsorbed and absorbed on the superabsorbent resin particles during the hydration treatment step due to the too high humidity, and the moisture absorption ability, which is the initial purpose of the superabsorbent resin particles, may be reduced.

[0042] The hydration treatment may be carried out for 3 to 15 minutes, more specifically, within 3 to 10 minutes. When the hydration treatment is carried out for less than 3 minutes, a sufficient amount of water cannot be adsorbed, and the anti-caking agent described below cannot be attached to the superabsorbent resin particles. In contrast, when the hydration treatment is carried out for more than 15 minutes, excessive water is adsorbed to the superabsorbent resin particles due to the long hydration treatment, and viscosity occurs between the superabsorbent resin particles in a state where the amount of water is larger than that of the anti-caking agent, making it difficult to prevent caking.

[0043] The hydration treatment is carried out under the above-mentioned conditions, and the means for creating this atmosphere can be, for example, a thermo-hygrostat or a method of directly spraying moisture. By such hydration treatment, moisture can be adsorbed on the surface of the highly water-absorbent resin particles. The adsorbed moisture can diffuse into the interior of the highly water-absorbent resin particles.

[0044] The weight of the water adsorbed to the highly water-absorbent resin particles by the hydration treatment may be 1 to 4 parts by weight per 100 parts by weight of the highly water-absorbent resin particles. Specifically, the weight may be 2 to 3 parts by weight.

[0045] If the moisture content is less than 1 part by weight, too little moisture is adsorbed on the surface of the superabsorbent resin particles, making it difficult for the anti-caking agent described below to sufficiently adhere to the surface of the superabsorbent resin particles, which may cause inconvenience in performing the role of the anti-caking agent to reduce the aggregation between the superabsorbent resin particles, resulting in a decrease in anti-caking efficiency.

[0046] If the moisture content is more than 4 parts by weight, the moisture may be excessively adsorbed on the surface of the superabsorbent resin particles by the hydration treatment, and the initially intended absorption performance of the superabsorbent resin particles may be reduced. Therefore, it may be difficult to achieve the desired level of absorption performance of the final superabsorbent resin composite. In addition, the excess moisture adsorbed compared to the caking inhibitor may cause viscosity and irreversible aggregation between the superabsorbent resin particles, which may result in caking.

[0047] Here, the amount of adsorbed water can be measured according to the International Organization for Standardization (ISO) 171904-4:2001 method.

[0048] Next, according to one embodiment of the present invention, a step of mixing the hydrated superabsorbent resin particles with an anti-caking agent and attaching the anti-caking agent to the hydrated superabsorbent resin particles is performed. As described above, the anti-caking agent can be attached uniformly to the superabsorbent resin particles by the hydration treatment, and the anti-caking agent can be attached to the superabsorbent resin particles with a strong adhesive strength. This can increase the anti-caking efficiency.

[0049] The caking inhibitor may be one or more of fumed silica, alumina, silica, and titania. Here, the caking inhibitor may be an inorganic material that does not generally absorb moisture, and examples of such inorganic materials include silica, fumed silica, clay, alumina, silica-alumina composites, titania, zinc oxide, and silicate, and any one or a mixture of two or more of these may be used. Unlike superabsorbent resin particles, the inorganic material does not absorb moisture in the air, and therefore, it is possible to prevent aggregation between particles due to excessive moisture adsorption of the superabsorbent resin particles.

[0050] The particle size of the anti-caking agent may be, for example, 3 μm to 30 μm in the case of fumed silica in relation to the particle size of the highly water-absorbent resin particles, where the particle size can be measured by a dry particle size analyzer Mictrotac S3500.

[0051] Meanwhile, the mixing of the hydrated superabsorbent resin particles and the caking inhibitor of the present invention may be performed immediately after the hydration of the superabsorbent resin particles or within 6 hours after the hydration. Here, "immediately after the hydration" may mean immediately after the completion of the hydration or within 2 minutes after the completion of the hydration. More specifically, when the mixing is performed immediately after the hydration, the caking inhibitor is uniformly applied to the surface of the hydrated superabsorbent resin particles, and the anti-caking efficiency of the caking inhibitor can be maximized. When the mixing is performed within 6 hours after the hydration, the attractive force between the hydrated superabsorbent resin particles and the caking inhibitor is strong, and the adhesive force can be increased. Therefore, it is possible to prevent the superabsorbent resin particles from absorbing a large amount of moisture in the air and causing irreversible aggregation.

[0052] The amount of the caking inhibitor added to the mixture may be 0.05 parts by weight to 0.15 parts by weight with respect to 100 parts by weight of the superabsorbent resin particles. Specifically, the weight may be 0.08 parts by weight to 0.12 parts by weight. More specifically, when the weight of the caking inhibitor is 0.08 parts by weight or more, the caking inhibitor can effectively prevent the occurrence of aggregation between the superabsorbent resin particles that have absorbed moisture from the atmosphere. When the weight of the caking inhibitor is 0.12 parts by weight or less, the caking inhibitor is adsorbed in an appropriate amount relative to the weight of the superabsorbent resin particles, and the anti-caking efficiency does not decrease significantly even during long-term storage, and a good condition can be maintained. In addition, since a general caking inhibitor is an inorganic substance that does not absorb moisture, it is possible to prevent a decrease in the moisture absorption ability, which is the original function of the superabsorbent resin composite, caused by an excessive amount of inorganic substance adhering to the surface of the superabsorbent resin particles.

[0053] Here, the mixing may be performed by putting the hydrated superabsorbent resin particles and the anti-caking agent into a container, for example, a sealed container, and then stirring to mix them.

[0054] The mixing causes an electrostatic attraction between the superabsorbent resin particles and the anti-caking agent, and also increases the viscosity or adhesion of the superabsorbent resin particles after the water addition treatment, making it possible for the superabsorbent resin particles to adhere to the anti-caking agent.

[0055] The present invention will be described in more detail with reference to the following examples. However, the following examples are merely for the purpose of illustrating the present invention, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical idea of ​​the present invention, and the scope of the present invention is not limited thereto.

[0056] Working Example Example 1 (1) Manufacturing of superabsorbent resin particles In a 3 L glass container equipped with a stirrer and a thermometer, 100 g (1.388 mol) of acrylic acid, 0.26 g of polyethylene glycol diacrylate (PEGDA) as an internal crosslinking agent, 0.008 g of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide as a photopolymerization initiator, 0.20 g of sodium persulfate as a thermal polymerization initiator, and 123.5 g of 32% caustic soda (NaOH) solution as a neutralizer were mixed with water at room temperature to a solid content of 45.0 wt %, to prepare a composition.

[0057] The composition was then fed onto a conveyer belt 10 cm wide and 2 m long rotating at a speed of 10 cm / min, where the polymerization reaction was carried out for 20 minutes on the conveyer belt equipped with a light source, thereby obtaining a hydrogel polymer with a water content of 45% by weight.

[0058] Next, the hydrogel polymer was pulverized using a pulverizer. Next, the pulverized product was dried for 30 minutes with hot air at 185°C using an air-flow oven. Through the pulverization, drying and classification, a base resin powder was obtained.

[0059] A surface cross-linking solution prepared by mixing water, methanol, and ethylene glycol diglycidyl ether as a surface cross-linking agent was added to 100 g of the base resin powder, and then a surface cross-linking reaction was carried out at 198° C. Then, the powder was pulverized and classified to produce 150 g of highly water-absorbent resin particles having a particle size of 150 to 850 μm.

[0060] (2) Manufacturing of superabsorbent resin composite 150 g of the superabsorbent resin particles produced in the above superabsorbent resin particle production method were uniformly spread on a SUS tray measuring 240 mm x 180 mm x 10 mm and placed in a thermohygrostat. The thermohygrostat performed a hydration treatment for 10 minutes under conditions of 40°C and 80% RH, and 3 g of water (2% by weight of water relative to 100% by weight of the superabsorbent resin particles) was adsorbed into the 150 g of superabsorbent resin particles placed in the thermohygrostat. The amount of water adsorption was measured in accordance with the International Organization for Standardization (ISO) 17190-4:2001 method.

[0061] Thereafter, the superabsorbent resin particles that had been hydrated for less than 2 minutes (immediately after hydration) and 0.15 g of fumed silica (0.10 wt% fumed silica per 100 wt% superabsorbent resin particles) were placed in the sealed container. The sealed container was shaken and mixed to adhere the hydrated superabsorbent resin particles and fumed silica. Thus, a superabsorbent resin composite in which the hydrated superabsorbent resin particles and fumed silica were adhered to each other was produced.

[0062] Example 2 A superabsorbent resin composite was produced using the same method as in Example 1, except that the hydration treatment was carried out for 12 minutes to adsorb 4.5 g of moisture (3% by weight of moisture relative to 100% by weight of superabsorbent resin particles) onto the superabsorbent resin particles.

[0063] Example 3 A superabsorbent resin composite was produced using the same method as in Example 1, except that the hydration treatment was carried out for 14 minutes to adsorb 6 g of moisture (4% by weight of moisture relative to 100% by weight of the superabsorbent resin particles) onto the superabsorbent resin particles.

[0064] Example 4 A superabsorbent resin composite was produced in the same manner as in Example 1, except that 0.08 g of fumed silica (0.05% by weight of fumed silica relative to 100% by weight of superabsorbent resin particles) was added to the sealed container.

[0065] Example 5 A superabsorbent resin composite was produced in the same manner as in Example 1, except that 0.23 g of fumed silica (0.15% by weight of fumed silica relative to 100% by weight of superabsorbent resin particles) was added to the sealed container.

[0066] Example 6 A superabsorbent resin composite was produced using the same method as in Example 1, except that the hydration treatment in Example 1 was not performed in a thermo-hygrostat, but was performed by directly spraying water to adsorb 3 g of moisture (2% by weight of water relative to 100% by weight of superabsorbent resin particles) onto the superabsorbent resin particles.

[0067] Example 7 A superabsorbent resin composite was produced using the same method as in Example 1, except that the hydration treatment in Example 1 was not performed in a thermo-hygrostat, but was instead performed by directly spraying water to adsorb 4.5 g of water (3% by weight of water relative to 100% by weight of the superabsorbent resin particles) onto the superabsorbent resin particles.

[0068] Example 8 A superabsorbent resin composite was produced using the same method as in Example 1, except that the hydration treatment was carried out for 5 minutes to adsorb 0.8 g of moisture (0.5% by weight of moisture relative to 100% by weight of the superabsorbent resin particles) onto the superabsorbent resin particles.

[0069] Example 9 A superabsorbent resin composite was produced using the same method as in Example 1, except that the hydration treatment was carried out for 7 minutes to adsorb 1.5 g of moisture (1% by weight of moisture relative to 100% by weight of superabsorbent resin particles) onto the superabsorbent resin particles.

[0070] Example 10 A superabsorbent resin composite was produced using the same method as in Example 1, except that the hydration treatment was carried out for 15 minutes to adsorb 9 g of moisture (6% by weight of moisture relative to 100% by weight of the superabsorbent resin particles) onto the superabsorbent resin particles.

[0071] Comparative Example Comparative Example 1 A superabsorbent resin composite was produced in the same manner as in Example 1, except that superabsorbent resin particles that had not been subjected to the hydration treatment were used.

[0072] Comparative Example 2 A superabsorbent resin composite was produced in the same manner as in Example 1, except that fumed silica was not added or mixed.

[0073] Comparative Example 3 A superabsorbent resin composite was produced using the same method as in Example 1, except that the superabsorbent resin particles were mixed 24 hours after the hydration treatment, rather than immediately after the hydration treatment in Example 1.

[0074] Experimental Example The anti-caking (A / C) efficiency of the superabsorbent resin composites prepared in the above Examples and Comparative Examples was measured by the following method. Here, the anti-caking efficiency was measured after storing the superabsorbent resin composites prepared in the above Examples and Comparative Examples in a sealed container for 4 hours, and the results are shown in Table 1 below.

[0075] [Table 1]

[0076] The anti-caking efficiency of the superabsorbent resin composite manufactured by the above-mentioned manufacturing method of the superabsorbent resin composite was measured by the following mathematical formula 1. Here, the anti-caking efficiency was measured while maintaining the moisture absorption at 38% to 44%, thereby ensuring the reproducibility of the anti-caking efficiency analysis. The moisture absorption was controlled by the following mathematical formula 2.

[0077]

number

[0078]

number

[0079] In the above formulas 1 and 2, W1 is the weight of a 57 mm aluminum dish, W2 is the weight of a sample of 0.76 g to 0.84 g of the superabsorbent polymer composites prepared in Examples 1 to 10 and Comparative Examples 1 to 3, and W3 is the total weight of the W1 dish and the W2 superabsorbent polymer composites placed on the dish, which were hydrated for 10 minutes under conditions of 80°C and 95% RH in a thermohygrostat. The hydrated superabsorbent polymer composites were placed in a 1400 μm mesh for each dish, and a sieve shaker was operated for 10 seconds under conditions of an amplitude of 1.0 mm / g. Finally, the weight of the superabsorbent polymer composites that passed through the 1400 μm mesh was measured and shown as W4.

[0080] As shown in Table 1, it was confirmed that the anti-caking efficiency of the Examples was significantly higher than that of the Comparative Examples. This confirmed that the anti-caking efficiency could be maximized by subjecting the superabsorbent resin particles to a hydration treatment. It was also found that the adhesion strength between the superabsorbent resin particles and the caking inhibitor was increased by the hydration treatment.

[0081] In addition, in Comparative Example 1, a caking inhibitor was mixed with non-hydration-treated superabsorbent resin particles, and it was confirmed that the anti-caking efficiency was significantly lower than that of Examples 1 to 3 and 6 to 10, in which the same 0.15 g (0.10 wt% fumed silica relative to 100 wt% superabsorbent resin particles) of fumed silica was added. This confirmed that the hydration treatment can have a significant effect on improving the anti-caking efficiency.

[0082] Comparative Example 2 is a superabsorbent resin composite in which no anti-caking agent was mixed in Example 1, and the anti-caking efficiency of the superabsorbent resin composite was measured. A superabsorbent resin composite to which no anti-caking agent was added is in a state in which moisture has already been adsorbed by the hydration treatment, and may be in a state in which viscosity occurs between superabsorbent resin particles and aggregation is formed. Since no anti-caking agent to prevent this was added, it was confirmed that the anti-caking efficiency was the worst among the examples and comparative examples of this experiment.

[0083] Meanwhile, in Comparative Example 3, the anti-caking efficiency of a superabsorbent resin composite prepared in the same manner as in Example 1 was measured, except that superabsorbent resin particles that had been hydrated for 24 hours were used instead of the superabsorbent resin particles immediately after hydration in Example 1. It was confirmed that the anti-caking efficiency of Comparative Example 3 was reduced by about 49% compared to Example 1. Therefore, when the superabsorbent resin particles and the fumed silica were mixed together, it was confirmed that the fumed silica was not strongly attached to the superabsorbent resin particles when the superabsorbent resin particles that had been hydrated for one day were used as in Comparative Example 3. Therefore, it was confirmed that the caking problem, which is the role of the caking inhibitor, could not be solved, and the anti-caking efficiency of Comparative Example 3 was significantly reduced.

Claims

1. providing superabsorbent resin particles comprising a crosslinked polymer of a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group and an internal crosslinking agent; a step of subjecting the superabsorbent resin particles to a hydration treatment to cause the superabsorbent resin particles to adsorb moisture; mixing the hydrated superabsorbent resin particles with an anti-caking agent to deposit the anti-caking agent on the hydrated superabsorbent resin particles; The caking inhibitor is at least one of fumed silica, alumina, silica, and titania; The hydration treatment is carried out by placing the highly water-absorbent resin particles in a thermo-hygrostat under conditions of 80% RH to 95% RH, The mixing of the hydrated superabsorbent resin particles and the caking inhibitor is carried out within 2 minutes after the hydration of the superabsorbent resin particles; The method for producing a superabsorbent resin composite, wherein the weight of the water adsorbed to the superabsorbent resin particles by the hydration treatment is 1 to 4 parts by weight per 100 parts by weight of the superabsorbent resin particles.

2. The method for producing a superabsorbent resin composite according to claim 1, wherein the hydration treatment is carried out under conditions of 25°C to 80°C.

3. The method for producing a superabsorbent resin composite according to claim 1, wherein the hydration treatment is carried out for 3 to 15 minutes.

4. 2. The method for producing a superabsorbent resin composite according to claim 1, wherein the weight of the anti-caking agent added during the mixing is 0.05 to 0.15 parts by weight per 100 parts by weight of the superabsorbent resin particles.

5. The method for producing a superabsorbent resin composite according to claim 1 , wherein the water-soluble ethylenically unsaturated monomer is (meth)acrylic acid or a salt thereof.

Citation Information

Patent Citations

  • Manufacturing method of super absorbent resin

    CN101768237A

  • Water-absorbent

    JP1986016903A

  • Manufacture of liquid-absorptive composite

    JP1988267435A

  • Particulate water absorbent mainly composed of water absorbing resin, manufacturing method therefor, and absorptive article

    JP2006068731A

  • Particulate water absorbing agent with water absorbing resin as main component

    JP2012143755A